2016
DOI: 10.1002/pip.2739
|View full text |Cite
|
Sign up to set email alerts
|

Large area tunnel oxide passivated rear contact n‐type Si solar cells with 21.2% efficiency

Abstract: This paper reports on the implementation of carrier-selective tunnel oxide passivated rear contact for high-efficiency screen-printed large area n-type front junction crystalline Si solar cells. It is shown that the tunnel oxide grown in nitric acid at room temperature (25°C) and capped with n + polysilicon layer provides excellent rear contact passivation with implied open-circuit voltage iV oc of 714 mV and saturation current density J 0b ′ of 10.3 fA/cm 2 for the back surface field region. The durability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…In this case, for example, a high‐temperature firing process is required to enable the conductive metal electrode material to penetrate the dielectric layers, which forms a local transport path. [ 15,16 ] In addition, the deposition of dielectric passivation materials always requires high‐vacuum equipment, such as plasma‐enhanced chemical vapor deposition (PECVD) and atomic layer deposition (ALD). Thus, for the future development of low‐cost clean energy sources, a new technical strategy, i.e., using only one material that can passivate interfacial electron traps while conducting carriers, is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, for example, a high‐temperature firing process is required to enable the conductive metal electrode material to penetrate the dielectric layers, which forms a local transport path. [ 15,16 ] In addition, the deposition of dielectric passivation materials always requires high‐vacuum equipment, such as plasma‐enhanced chemical vapor deposition (PECVD) and atomic layer deposition (ALD). Thus, for the future development of low‐cost clean energy sources, a new technical strategy, i.e., using only one material that can passivate interfacial electron traps while conducting carriers, is needed.…”
Section: Introductionmentioning
confidence: 99%
“…An example of a bifacial, n ‐type, large‐area (ie, 239 cm 2 ), screen‐printed, passivating contact cell demonstrating efficiencies up to 21.3% using fire‐through metallization on the front and rear sides can be found in the study of Stodolny et al The highest cell efficiency found in the literature for a large‐area (ie, 244.3 cm 2 ), bifacial, passivating contact cell with screen‐printed, and fired metal contacts is currently at 21.5% . On the other hand, an n ‐type, large‐area, monofacial solar cell with an efficiency of 21.4% was reported with a screen‐printed front but with full‐area thermally evaporated silver (Ag) on the rear . Hybrid schemes that use a passivating contact capped by transparent conductive oxides (TCOs) recently demonstrated a best cell efficiency of 22.3% on large‐area cells; however, it must be noted that these cells use low‐temperature screen‐printed Ag metallization at the front and rear .…”
Section: Introductionmentioning
confidence: 99%
“…21 On the other hand, an n-type, large-area, monofacial solar cell with an efficiency of 21.4% was reported with a screen-printed front but with full-area thermally evaporated silver (Ag) on the rear. 22 Hybrid schemes that use a passivating contact capped by transparent conductive oxides (TCOs) recently demonstrated a best cell efficiency of 22.3% on large-area cells; however, it must be noted that these cells use low-temperature screen-printed Ag metallization at the front and rear. 23 Hence, there is still some work needed to make passivating contact cell technology accessible to the current PV industry where high-temperature screen-printed metallization schemes dominate.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, passivating and carrier-selective contacts have pushed the efficiency of crystalline silicon (c-Si) solar cells to new record efficiencies. [1][2][3][4][5][6] One of the most promising approaches to such structures is the tunnel oxide passivated contact (TOPCon) process, which utilizes an ultrathin interfacial oxide (12-15 Å) at the interface in combination with a heavily doped silicon (poly-Si) or a silicon-rich silicon carbide (SiC x ) thin film. Tube furnace direct plasma-enhanced chemical vapor deposition (PECVD) reactors can be an appealing technology enabling high throughput deposition of the silicon thin film.…”
Section: Introductionmentioning
confidence: 99%